2007
DOI: 10.1002/cm.20213
|View full text |Cite
|
Sign up to set email alerts
|

An actin‐stabilizing peptide conjugate deduced from the major outer sheath protein of the bacterium Treponema denticola

Abstract: A synthetic peptide conjugated to bovine serum albumin, P34(BSA), based on a 10-mer in the deduced amino acid sequence of the major outer sheath protein of Treponema denticola, was found to stabilize actin filaments of fibroblasts. Pretreatment of cells with P34(BSA) inhibited the actin disruption induced by cytochalasin D and latrunculin B. P34(BSA) was taken up by the cells and localized among actin filaments. P34(BSA) bound actin from fibroblast lysates, and cell exposure to P34(BSA) led to the activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…These findings prompted further studies of the cell-binding, translocation, and signalling of the P34 BSA conjugate. We reported previously that P34 BSA was internalized by fibroblasts but not by the same endocytic pathway as transferrin, that it bound and aggregated actin filaments in vitro, and that it activated RhoA, a key regulator of actin filament dynamics [Subauste et al, 2000;Amin et al, 2007]. Yet, the actual pathways and mechanisms that accounted for its profound effect on actin stress fibers were not investigated.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…These findings prompted further studies of the cell-binding, translocation, and signalling of the P34 BSA conjugate. We reported previously that P34 BSA was internalized by fibroblasts but not by the same endocytic pathway as transferrin, that it bound and aggregated actin filaments in vitro, and that it activated RhoA, a key regulator of actin filament dynamics [Subauste et al, 2000;Amin et al, 2007]. Yet, the actual pathways and mechanisms that accounted for its profound effect on actin stress fibers were not investigated.…”
Section: Introductionmentioning
confidence: 89%
“…We have recently identified a bioactive peptide of Msp, which, when conjugated to BSA as P34 BSA , promotes actin stress fiber formation and actin filament stability in cells exposed to the actin inhibitors cytochalasin D and latrunculin B [Amin et al, 2007]. P34 BSA was unique in this regard among Msp-deduced synthetic peptide-BSA conjugates, and its activity depended on its lysine residues.…”
Section: Introductionmentioning
confidence: 98%
“…T. denticola major outer sheath protein (Msp) is one of its most important virulence factors in contributing to the disease progression. This membrane protein modulates neutrophil signaling pathways involved in cytoskeletal dynamics that are relevant in chemotaxis and phagocytosis [70]. Msp controls neutrophil cytoskeletal functions like migration, adhesion, and cell shape.…”
Section: Treponema Denticolamentioning
confidence: 99%
“…Tobacco-induced susceptibility to periodontitis was also believed to be associated (198,200,201), which was contradicted in a recent study which showed that smokers with periodontitis has decreased bacterial diversity (221).…”
Section: Smoking and Periodontal Pathogensmentioning
confidence: 99%
“…It is also one of the immunodominant T. denticola antigens recognized by human serum antibodies (196). Msp interaction leads to actin remodeling and reorganization in host cells, which is likely how it impairs neutrophil chemotaxis and phagocytic activity (197)(198)(199)(200).…”
Section: Major Sheath Protein (Msp)mentioning
confidence: 99%